Employees' Reactions and Factors in the Implementation of ISO 9000 in Manufacturing Companies - Osman, Mohd Rasid; Mohd. Yusuff, Rosnah; Megat Ahmad, Megat Mohamad Hamdan; Chew, C. Y. (Universiti Putra Malaysia Press, 2001)
ISO 9000 has taken a size able portion of the global industry, especially in the manufacturing industry by storm since its inception in 1987. Many problems associated with ISO 9000 implementation emanated from the reliance of belief or faith while neglecting the direct relationship to employee's roles and responsibilities. This study explores and discusses issues in the implementation of ISO 9000 at the employees' level. The issues encompass employees' reaction towards ISO 9000 and general employee factors in the implementation of ISO 9000. The issues were gathered from existing literature and verified by local manufacturing companies via questionnaires. The questionnaire response rate was 38.8% or 50 responses out of the 129 questionnaires sent. The results from the findings indicated the important employee issues in the successful implementation of ISO 9000 are commitment, teamwork, training and involvement, amongst others. It is believed this study will further enhance understanding and place importance in the issues concerning employees of a company implementing ISO 9000.